1993
DOI: 10.1002/food.19930370503
|View full text |Cite
|
Sign up to set email alerts
|

Effect of freezing and mincing technique on microbial load of minced meat

Abstract: This experiment was carried out to explain the variation between the use of either fresh or frozen meat cuts in manufacturing of minced meat; in this connection the role of the mincer and the hygienic condition of handling as well as of the temperature under which the raw material and product was handled should be investigated. The achieved results indicated that the minced meat manufactured from fresh meat has low microbial load as compared with that produced from frozen one. However, the mincing at butcher's… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 18 publications
(10 reference statements)
0
6
0
Order By: Relevance
“…In our case, the high TVC reflected the clear impact of the meat background (thawed meat cuts that were aerobically processed in a traditional butchery). Bacterial load is higher in the minced meat obtained from thawed rather than fresh pieces because muscle membranes are damaged by the freezing–thawing cycle, which appears to reduce the lag phase of bacterial growth (Khalafalla et al ; Leygonie et al ). Similarly, the counts of all the bacterial groups increased ( P < 0.01) in the patties throughout storage, except for Pseudomonas spp.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In our case, the high TVC reflected the clear impact of the meat background (thawed meat cuts that were aerobically processed in a traditional butchery). Bacterial load is higher in the minced meat obtained from thawed rather than fresh pieces because muscle membranes are damaged by the freezing–thawing cycle, which appears to reduce the lag phase of bacterial growth (Khalafalla et al ; Leygonie et al ). Similarly, the counts of all the bacterial groups increased ( P < 0.01) in the patties throughout storage, except for Pseudomonas spp.…”
Section: Resultsmentioning
confidence: 99%
“…Among the products tested in lambs, a dietary rosemary extract (RE) containing carnosic acid and carnosol has been seen to lead to the deposition in muscle of a diterpenic metabolite derived from the carnosol with antioxidant and antimicrobial potential effects (Jordán et al ). Other studies suggest that the antimicrobial potential of RE would not be well used when lamb fillets are packed under a bacteriostatic atmosphere (Bañón et al ; Serrano et al ; Ortuño et al ), hence the interest in knowing whether RE is able to delay microbial spoilage in meat products that present a high microbial risk, such as raw patties made from frozen–thawed pieces (Khalafalla et al ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the mean values of these samples were far greater than those reported for meat obtained at a retail shop, i.e., 2 log CFU/g [24]. Khalafalla et al [25] also reported lower counts of staphylococci, i.e., 3 log CFU/g in in hamburger meat samples.…”
Section: Enumeration and Satisfactory Level Of Staphylococcus Aureusmentioning
confidence: 79%
“…Consumers are unlikely to notice the changes that occur in frozen meat ( Ambrosiadis et al ., 1994 ), namely protein denaturation and water loss ( Mackie, 1993), so the extent of this problem is unknown. However, as there is a finite health risk to consumers if the meat has been repeatedly frozen and thawed ( Bedinghaus & Ockerman 1991; Panebianco et al ., 1991 ; Khalafalla et al ., 1993 ), the problem of authenticating meat is a health and safety issue as well as an economic one. Enzymatic methods that can detect protein denaturation have been used to authenticate meat, but have proved to be unreliable ( Mietsch et al ., 1994 ; Ellerbroek et al ., 1995 ).…”
Section: Introductionmentioning
confidence: 99%